DEVELOPMENT OF THE HUMAN SKELETAL SYSTEM AND AGE-RELATED CHANGES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The human skeletal system undergoes continuous development and transformation from embryonic stages through old age. These changes are influenced by genetic, hormonal, nutritional, and environmental factors. This article examines the stages of skeletal development, including ossification processes, growth patterns during childhood and adolescence, peak bone mass achievement, and degenerative changes associated with aging. The study also explores the physiological and structural changes that occur in bones, cartilage, and joints over time. Understanding these processes is crucial for preventing skeletal disorders such as osteoporosis and fractures, and for promoting lifelong musculoskeletal health.